Ordu Ethnographical Museum to Display Ancient Masks, Busts - Hürriyet Daily News (Les Carnets de l’ACoSt)
More than 20 busts and masks, which were unearthed in the 2,300-year-old Ordu Kurul Castle and estimated to be 2,100 years old, will be exhibited at the Ordu Paşaoğlu Mansion and Ethnography Museum.